2014
DOI: 10.4172/2167-0846.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Intra Uterine Fetal Death And Some Related Factors: A Silent Tragedy In Southeastern Iran

Abstract: Objective: To determine the incidence, and some causes of intra uterine fetal death (IUFD). Methods:This was a prospective observational study of all stillbirths over 2 years from April 2011 to April 2013 at the Imam Ali University Teaching Hospital of zahedan, Iran. The variables studied were the following: demographic characteristic, fetal factors and maternal factors. Data was collected prospectively by directly interviewing the pregnant women and from the medical chart. Data were analyzed using SPSS (Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The study also showed that the chance of stillbirth reduced with increasing gestational age and birth weight. These results are consistent with the results of previous studies (8,10,17). Congenital malformation increased the incidence of stillbirth by about nine times, which is consistent with the results of Walfisch et al study (14).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The study also showed that the chance of stillbirth reduced with increasing gestational age and birth weight. These results are consistent with the results of previous studies (8,10,17). Congenital malformation increased the incidence of stillbirth by about nine times, which is consistent with the results of Walfisch et al study (14).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, there are different reports on the prevalence of stillbirth in different cities of Iran. The prevalence of stillbirth was 11.7 in Babol (7), 19.8 in Arak (16), 40 in Ahwaz (9), and 88.7 in Zahedan (per 1000 births) (8). The estimated prevalence of stillbirths in this study was very close to the national estimated rate (13).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…9 Many studies have stated hypertensive disorders of the pregnancy to be a most common risk factor of IUFD. 3,10,11…”
Section: Resultsmentioning
confidence: 99%
“…While the second most common factor varies; in Jindal et al severe IUGR, in Rathava et al Abruptio placenta, in Divya et al it was Hypothyroidism 7,10,11. This variation may be as general common factors among pregnant in different regions.…”
mentioning
confidence: 96%